The utilization of the Indonesian Karst Museum for Social Sciences learning in middle school - Wibowo, Satriyo; Dhewantoro, Happri Novriza Setya (Universitas Negeri Yogyakarta, 2024)
This study seeks to explore how the Indonesian Karst Museum can be used in creating educational materials for Social Studies within the Gunung Sewu UNESCO Global Geopark area, while also exploring the museum's potential as an educational medium to enhance students' understanding of geology and karst ecosystems. The research employs a qualitative method through observations and interviews with museum staff and local Social Studies teachers. The findings reveal that the museum contains numerous relevant collections that can be incorporated into the Social Studies curriculum, though challenges in implementation were also identified. The use of the Indonesian Karst Museum in developing teaching materials for Social Studies within the Gunung Sewu area offers numerous benefits. Beyond enriching students' learning experiences, the museum also helps connect theoretical knowledge to daily life. By adopting an innovative and interactive approach, the museum has the potential to inspire Social Studies education. It is anticipated that it will lay the foundation for the development of more relevant teaching materials, optimize the use of local heritage in teaching practices, and engage students while raising awareness about the importance of preserving the karst environment in the region.